2003
DOI: 10.1017/s0954579403000476
|View full text |Cite
|
Sign up to set email alerts
|

What can developmental disorders tell us about the neurocomputational constraints that shape development? The case of Williams syndrome

Abstract: The uneven cognitive phenotype in the adult outcome of Williams syndrome has led some researchers to make strong claims about the modularity of the brain and the purported genetically determined, innate specification of cognitive modules. Such arguments have particularly been marshalled with respect to language. We challenge this direct generalisation from adult phenotypic outcomes to genetic specification, and consider instead how genetic disorders provide clues to the constraints on plasticity that shape the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 90 publications
0
35
0
5
Order By: Relevance
“…For instance, Robinson, Mervis, and Robinson (2003) reported that 10-year-olds with Williams syndrome relied on their working memory to a greater extent than grammar-matched typical children during language tasks, even when differences in receptive vocabulary skills were covaried. This finding suggests a deviant pattern of language development (see also Karmiloff-Smith & Thomas, 2003). However, other research has provided evidence for a delayed pattern of language production.…”
Section: Williams Syndromementioning
confidence: 88%
See 4 more Smart Citations
“…For instance, Robinson, Mervis, and Robinson (2003) reported that 10-year-olds with Williams syndrome relied on their working memory to a greater extent than grammar-matched typical children during language tasks, even when differences in receptive vocabulary skills were covaried. This finding suggests a deviant pattern of language development (see also Karmiloff-Smith & Thomas, 2003). However, other research has provided evidence for a delayed pattern of language production.…”
Section: Williams Syndromementioning
confidence: 88%
“…Results of profile analyses within different populations have been especially helpful in debunking stereotypes about different etiologic groups and have highlighted methodological caveats for future research, including the need for longitudinal research and the continued need to evaluate multiple dimensions of language (e.g., vocabulary/semantics, grammar/syntax, and pragmatics) in diverse groups. This research has also fueled and sparked continuing debates among researchers regarding the age-old philosophical question of the ontogenetic association between language and cognition (e.g., Elman et al, 1996;Karmiloff-Smith & Thomas, 2003;Thelen & Bates, 2003).…”
Section: Need For Translational Research On Early Language Developmentmentioning
confidence: 99%
See 3 more Smart Citations